Evaluation of whole blood thiamine pyrophosphate concentrations in critically ill patients receiving chronic diuretic therapy prior to admission to Turkish intensive care units: A pragmatic, multicenter, prospective study - Gundogan, Kursat; Sahin, Gulsah G.; Ergul, Serap S.; Ozer, Nurhayat T.; Temel, Sahin; Akbas, Turkay; Ziegler, Thomas R. (W B Saunders Co-Elsevier Inc, 2023)
Background/Objectives: Thiamine plays a pivotal role in energy metabolism. The aim of the study was to deter-mine serial whole blood TPP concentrations in critically ill patients receiving chronic diuretic treatment before ICU admission and to correlate TPP levels with clinically determined serum phosphorus concentrations.Subjects/Methods: This observational study was performed in 15 medical ICUs. Serial whole blood TPP concen-trations were measured by HPLC at baseline and at days 2, 5 and 10 after ICU admission. Results: A total of 221 participants were included. Of these, 18% demonstrated low TPP concentrations upon admission to the ICU, while 26% of participants demonstrated low levels at some point during the 10-day study period. Hypophosphatemia was detected in 30% of participants at some point during the 10-day period of observation. TPP levels were significantly and positively correlated with serum phosphorus levels at each time point (P < 0.05 for all).Conclusions: Our results show that 18% of these critically ill patients exhibited low whole blood TPP concen-trations on ICU admission and 26% had low levels during the initial 10 ICU days, respectively. The modest correlation between TPP and phosphorus concentrations suggests a possible association due to a refeeding effect in ICU patients requiring chronic diuretic therapy.
Keywords: Critical illness; Diuretics; Refeeding syndrome; Thiamine